2016
DOI: 10.1007/s00405-016-4250-8
|View full text |Cite
|
Sign up to set email alerts
|

The pre-treatment neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and red cell distribution width predict prognosis in patients with laryngeal carcinoma

Abstract: The aim of this study was to identify the potential prognostic roles of the preoperative neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and red cell distribution width (RDW) in patients with laryngeal squamous cell carcinoma (LSCC). 81 patients who underwent surgery for the larynx carcinoma were enrolled in the study. NLR, PLR and RDW were used as outcome measures. Local recurrence was detected in 30 (37.0 %) patients and neck lymph node metastasis was detected 6 (7.4 %) patients dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 24 publications
2
71
3
1
Order By: Relevance
“…Therefore, meta-analyses were conducted with a random effect model, using Comprehensive Meta-Analysis version 2 (Biostat, Englewood, NJ). However, only 4 studies 38,42,44,46 were subjected to subgroup analyses for disease sites because the other studies reported the HRs of patients with different affected sites together. Most of the included studies dichotomized patients into 2 groups according to the platelet count or PLR.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, meta-analyses were conducted with a random effect model, using Comprehensive Meta-Analysis version 2 (Biostat, Englewood, NJ). However, only 4 studies 38,42,44,46 were subjected to subgroup analyses for disease sites because the other studies reported the HRs of patients with different affected sites together. Most of the included studies dichotomized patients into 2 groups according to the platelet count or PLR.…”
Section: Discussionmentioning
confidence: 99%
“…The HRs for DSS were reported in 3 studies and ranged from 0.95 to 1.62; none were statistically significant 37,39,51 ( Figure 2B). Table 2 37,38,[41][42][43][44][45][46]51 shows the characteristics of the included studies for PLR analysis. The pooled HR for DSS was 1.13 (95% CI 0.90-1.43), and the result was not statistically significant.…”
Section: Platelet Countmentioning
confidence: 99%
See 3 more Smart Citations